Dynamiczne Linie Wpływu Ugięć Wieloczęściowego Pasma na Sprężystym Podłożu - Skarżyński, R. (Engineering Transactions, 1970)
In this paper are derived the equations of motion of a compound band having an arbitrary number of elements connected with each other by articulated joints or in a continuous manner (on supports), and resting on an elastic base. Along the band a load is displaced in a form of a single force or a system of connected forces. The solution of the problem is obtained by the method of generalized series of Fourier’s eigen-functions. In both structures, the solution is brought to set of linear equations and is illustrated by an example. The accepted dynamic scheme can be a model for a communication surface.